2018
DOI: 10.1016/j.diabres.2018.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metformin use and other antihyperglycemic therapies after insulin initiation in patients with type 2 diabetes

Abstract: The vast majority of patients with type 2 diabetes continue metformin after insulin initiation, consistent with guidelines. Other antihyperglycemics are frequently continued along with insulin, and further research is needed to determine which, if any, patients may benefit from this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…[7] This finding is also in agreement with prior studies that found a high proportion of metformin continuation and reported metformin to be the most commonly used therapy in combination with insulin. [12, 13] There is a wealth of evidence to support the benefits of continuing metformin in this setting, including its association with better glycemic control, lower weight gain and lower insulin doses. [8, 14, 15]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] This finding is also in agreement with prior studies that found a high proportion of metformin continuation and reported metformin to be the most commonly used therapy in combination with insulin. [12, 13] There is a wealth of evidence to support the benefits of continuing metformin in this setting, including its association with better glycemic control, lower weight gain and lower insulin doses. [8, 14, 15]…”
Section: Discussionmentioning
confidence: 99%
“…The high continuation rates of diabetes medications other than metformin after the transition to insulin were consistent with the previous study on this topic. [12] High rates of continuation were particularly surprising for insulin secretagogues. Use of sulfonylureas or thiazolidinediones in combination with insulin may cause more hypoglycemic episodes and greater weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study done in the US reported more than 70% patients taking metformin before insulin therapy and 80.3% patients continued it after insulin initiation. The proportion of metformin use after insulin therapy was also higher (63.8%) in Pilla et al's study (23). Another study with commercial insurance data also reported 72.7% patients taking metformin before insulin initiation and metformin was continued in 84.6% patients after insulin therapy.…”
Section: Secondary Outcomesmentioning
confidence: 73%
“…Another potential explanation for this observation is common underdosing of insulin due to fear of causing hypoglycaemia 20 . Furthermore, initiation of insulin treatment is sometimes accompanied by the withdrawal of other glucose‐lowering drugs, which may compromise optimal glycaemic control 21,22 …”
Section: Discussionmentioning
confidence: 99%